Student Problems In Time Management At Online Learning To Support Student Achievement In Class - Sri Noflesti; Genio Czar Althariqy (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The purpose of this research is to know the student problem in time management, the data is get from the student who was learn by using online learning in class. The data is using questionnarre and collect by google form, this research using three tests to the data that is validity, reliability and percentage. The result of the data is valid, reliable and ten points of data is proven true by the percentage. With this research the student can knowing first what the problem that will happen in online learning when the student wat to do time management.Keyword: Problem, Online Learning, Student, Time Management